The intermediate filament protein, vimentin, is a regulator of NOD2 activity. Issue 5 (8th June 2012) - Stevens, Craig; Henderson, Paul; Nimmo, Elaine R; Soares, Dinesh C; Dogan, Belgin; Simpson, Kenneth W; Barrett, Jeffrey C; ,; Wilson, David C; Satsangi, Jack
Abstract : Objective: Mutations in the nucleotide-binding oligomerisation domain-containing protein 2 (NOD2) gene remain the strongest genetic determinants for Crohn's disease (CD). Having previously identified vimentin as a novel NOD2-interacting protein, the authors aimed to investigate the regulatory effects of vimentin on NOD2 function and the association of variants in Vim with CD susceptibility. Design: Coimmunoprecipitation, fluorescent microscopy and fractionation were used to confirm the interaction between NOD2 and vimentin. HEK293 cells stably expressing wild-type NOD2 or a NOD2 frameshift variant (L1007fs) and SW480 colonic epithelial cells were used alongside the vimentin inhibitor, withaferin A (WFA), to assess effects on NOD2 function using the nuclear factor-kappaB (NF-κB) reporter gene, green fluorescent protein-LC3-based autophagy, and bacterial gentamicin protection assays. International genome-wide association meta-analysis data were used to test for associations of single-nucleotide polymorphisms in Vim with CD susceptibility. Results: The leucine-rich repeat domain of NOD2 contained the elements required for vimentin binding; CD-associated polymorphisms disrupted this interaction. NOD2 and vimentin colocalised at the cell plasma membrane, and cytosolic mislocalisation of the L1007fs and R702W variants correlated with an inability to interact with vimentin. Use of WFA demonstrated that vimentin was required for NOD2-dependent NF-κB activation and muramyl dipeptide-induced autophagy induction, and that NOD2 and vimentin regulated the invasion and survival properties of a CD-associated adherent-invasive Escherichia coli strain. Genetic analysis revealed an association signal across the haplotype block containing Vim . Conclusion: Vimentin is an important regulator of NOD2 function and a potential novel therapeutic target in the treatment of CD. In addition, Vim is a candidate susceptibility gene for CD, supporting the functional data.